2000
DOI: 10.1021/jm9900218
|View full text |Cite
|
Sign up to set email alerts
|

Opiate Aromatic Pharmacophore Structure−Activity Relationships in CTAP Analogues Determined by Topographical Bias, Two-Dimensional NMR, and Biological Activity Assays

Abstract: Topographically constrained analogues of the highly mu-opioid-receptor-selective antagonist CTAP (H-D-Phe-c[Cys-Tyr-D-Trp-Arg-Thr-Pen]-Thr-NH(2), 1) were prepared by solid-phase peptide synthesis. Replacement of the D-Phe residue with conformationally biased beta-methyl derivatives of phenylalanine or tryptophan (2R,3R; 2R,3S; 2S,3R; 2S,3S) yielded peptides that displayed widely varying types of biological activities. In an effort to correlate the observed biological activities of these analogues with their st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…Among the known dehydroamino acids, dehydrophenylalanine is the most commonly used to modify bioactive peptides because it is the most stable and relatively easy to obtain. On the other hand, among topographically constrained amino acids, β‐methylphenylalanine is very often used as the phenyl ring commonly serves as a pharmacophore45–51. This is an important feature as the advances in structure–activity relationships have shown that restrictions not only of the conformations (ϕ,ψ torsion angles) but also of topographies (χ torsion angles) of a single amino acid residues can affect the bioactivities of peptides52.…”
Section: Resultsmentioning
confidence: 99%
“…Among the known dehydroamino acids, dehydrophenylalanine is the most commonly used to modify bioactive peptides because it is the most stable and relatively easy to obtain. On the other hand, among topographically constrained amino acids, β‐methylphenylalanine is very often used as the phenyl ring commonly serves as a pharmacophore45–51. This is an important feature as the advances in structure–activity relationships have shown that restrictions not only of the conformations (ϕ,ψ torsion angles) but also of topographies (χ torsion angles) of a single amino acid residues can affect the bioactivities of peptides52.…”
Section: Resultsmentioning
confidence: 99%
“…The elements of opioid peptides hypothesized to be responsible for their activities are a pair of aromatic amino acid residues, one in the N‐terminal position and another in either position 3 or 4 (110). Replacement of the d ‐Phe residue in CTAP with conformationally biased β‐methyl derivatives of Phe or Trp resulted in topographically constrained analogs that displayed widely varying types of biological activities (111). On the basis of the low‐energy conformations of these analogs, aromatic pharmacophore arrangements were discovered for opioid receptor activity.…”
Section: Somatostatin‐derived Ligands For Other G‐protein‐coupled Recmentioning
confidence: 99%
“…Unnatural amino acids are often employed to affect these constraints. In particular, stereospecific ␤-methyl substitution is a widely used technique for constraining aromatic side-chains [4][5][6]. Additionally, it is most advantageous to examine only stereochemically pure substances, thereby precluding ambiguous physicochemical and biological data that may arise from the testing of enantiomeric/diastereomeric mixtures.…”
Section: Resultsmentioning
confidence: 99%
“…Nuclear magnetic resonance (NMR) Spectroscopy was performed on a Bruker Avance 300 MHz spectrometer (Billerica, MA, USA) equipped with a 5 mm auto-switchable quad nucleus (QNP) probe at 25 • C. NMR data were collected in DMSO-d 6 and standard Bruker zg30 and noesyst NMR pulse programs were used for the 1 H and NOESY experiments, respectively. Chemical shifts are referenced to tetramethylsilane (TMS).…”
Section: Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation